Efektivitas Website Ecommerce Dalam Meningkatkan Kepercayaan Konsumen Terhadap Pembelian Motor Bekas - Haris, Adam; Sipayung, Muhammad Irfan Afandi; Harahap, Fauzi Syahputra; Sitakar, Tutur Arbaim; Siregar, Ridho Albar; Sulindawaty, Sulindawaty (CV. ITTC INDONESIA, 2024)
This study aims to analyze the effectiveness of the afair5second.my.id website in increasing consumer trust in purchasing used motorcycles. This website is designed to facilitate the process of buying and selling quality used motorcycles by providing information about products, company profiles, and WhatsApp and email contacts for communication with customers. By using a survey method to website users, this study measures the level of consumer trust based on aspects of information transparency, ease of access, and clarity of communication. The results of the study show that an informative and easily accessible website design contributes significantly to increasing consumer trust. The existence of a clear company profile and available direct contacts also strengthen consumer confidence in the credibility of the store. In conclusion, the afair5second.my.id website is effective in building consumer trust, especially in the used motorcycle market. This study provides recommendations for further development, such as adding consumer review features and quality certification, to increase the competitiveness of the website